If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 2h = 1 Solving 7 + 2h = 1 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 2h = 1 + -7 Combine like terms: 7 + -7 = 0 0 + 2h = 1 + -7 2h = 1 + -7 Combine like terms: 1 + -7 = -6 2h = -6 Divide each side by '2'. h = -3 Simplifying h = -3
| 6(k+4)-(5+9k)=-4k | | 7+5(1+2x)=-2(5+6x) | | 8(8x+4)=-32-7x | | 3x+2x+20x= | | 2y+4=-5 | | 15=-5(4-7x) | | 6(v+4)-2v=2(2v+2)-11 | | x-4x=2x+1-5x | | 3-0.5r=12 | | 6=-w/8 | | 3.4x-1.4=1.36-3.5x | | 3(2x-3)=6(x+1)-15 | | 21x-2=4(5x+3)-10 | | X+13=-14 | | .7x+.05(6-x)=.1(-88) | | |p-7|+13=5 | | s+2-3-16=0 | | 80=3x+19 | | 22+8x=-5+3(5x-5) | | -2(a-5)=27-2a | | 20(x-1)=-4(5-x)+16x | | y^2+11y-12=0 | | 12y^2-4y^4= | | 4x-2(x-7)=4 | | 6x^2+5x-8=-4 | | 43+63+57+4x=55 | | .18y+.04(y+6000)=1780 | | us+uz=t | | 7n=85n | | 2r-(-4+r)=7-2r | | 32y+5y=2 | | 6x-12+2x=7+8x-19 |